Living With a Religious Majority: Historical Dynamics of Christianity in Madura’s Muslim Society - Akhmad Siddiq; Karl James Villarmea (Pascasarjana IAIN Pontianak, 2026)
This article aims to describe the history of Christianity in Madura, Indonesia, and its relations with Islam as the religion of the Muslim majority. The data has been collected through observation and interviews, as well as documentation of academic references and the booklets of the local churches. This research found that Christianity has persisted in Madura for centuries through cultural routes such as migration, marriage, and personal choice. Despite its exclusivity as a European faith in the era of the Dutch, Christianity was consciously accepted by the Chinese community in Madura and even by some Madurese themselves. The history of Christianity in Madura is one of long acculturation and interfaith encounters based on social interaction. It has survived the historical flames since the beginning of the VOC period. It continues to be a significant factor in the construction of the current social life of the Madurese people. The implications of this research lie in its contribution to the study of interreligious coexistence and minority–majority relations in Indonesia. The originality and value of this study rest in its focus on Madura—an area largely neglected in Indonesian church history—thereby filling a gap in scholarship and providing new perspectives on the dynamics of Christianity within a predominantly Muslim cultural context. Christianity and Christians have become essential elements within the cultural, political, and economic social relations of contemporary Madura.